Punitive damages how juries decide - Sunstein, Cass R. (Chicago, [Ill.] : University of Chicago Press, 2002)
How do juries make decisions about punitive damages? The authors present the results of controlled experiments with more than 600 mock juries involving the responses of more than 8,000 jury-eligible citizens. Although juries tended to agree in their moral judgments about the defendant's conduct, they rendered erratic and unpredictable dollar awards. Using a wealth of new experimental data, and offering a host of provocative findings, this book documents a wide range of systematic biases in jury behaviour.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Exemplary damages -- United States; Jury -- United States; Law; United States of America, USA; Jurisprudence & general issues; Laws of specific jurisdictions & specific areas of law; Arbitration, mediation & alternative dispute resolution; Law of torts, damages & compensation